Performance of Kansas State University’s Cold and Large Patch-Tolerant Zoysiagrasses in the National Turfgrass Evaluation Program Test - Jack Fry; Manoj Chhetri (Kansas Agricultural Experiment Station Research Reports, 2021)
The National Turfgrass Evaluation Program (NTEP) Zoysia Test was planted in 2019 at the Kansas State University Olathe Horticulture Center, Olathe, KS. Since planting, three experimental genotypes developed at K-State (with cooperators noted below) have outperformed ‘Meyer’ in establishment rate, turf quality, drought tolerance, and fall color. Earlier research has demonstrated large patch tolerance in all three experimental genotypes.
Keywords: zoysiagrass; warm-season grasses